Experimental study of sloshing of liquid in a tank / Mahamad Hisyam Mahamad Basri - Mahamad Basri, Mahamad Hisyam (2005)
This thesis is presenting the development of experiment for the study of sloshing of liquid in a tank. Sloshing occurs when a partially filled tank of liquid goes through transient or steady external forces. Under such conditions, the free surface of the liquid may move and the liquid may impact on the walls of the tank, exchanging forces. These forces may cause numerous harmful and undesirable consequences in the operation of the vehicle, such as vehicle turn over. In this thesis the experimental results are catered towards validating the Computational Fluid Dynamic (CFD) simulation that has been done by PHOENICS.